High infestation of Cecropia pachystachya (Urticaceae) by the scarab beetle Macrodactylus pumilio Burm., 1855 (Coleoptera: Scarabaeidae) - Negrao, Helena; Barbosa, Milton; Fernandes, Geraldo W. (Entomological Communications, 2023)
Population outbreaks, although rare, hold significant ecological implications, particularly in short-lived organisms. These outbreaks are often triggered by changes in population control factors such as food availability, absence or reduction of natural enemies, diseases, or favourable climatic conditions. This study documents an infestation event where the scarab beetle Macrodactylus pumilio Burm., 1855 (Coleoptera: Scarabaeidae) heavily infested a specimen of Cecropia pachystachya Trécul. in, Serra do Cipó, Minas Gerais, Brazil. The infestation took place at the onset of the rainy season, which corresponded with the annual emergence of the beetles from the soil. We searched another nine fruiting trees within 100 m radius, none of which were infested. The estimated abundance of M. pumilio beetles on the infested tree reached 45,825 insect individuals. The insect is a known agricultural pest, affecting citrus, passion fruit, coffee plantations, and ornamental flowers. C. pachystachya, a pioneer tree commonly found in secondary forests of Latin America, may represent a potential alternative host for the beetles in the face of increasing pesticide use. This event may have significant implications for the population dynamics of C. pachystachya and highlights the importance of understanding the life cycle and behaviour of species of the genus Macrodactylus Dejean, 1821. Similar outbreaks have been reported in agricultural systems, emphasizing the need for precise knowledge to plan effective management strategies in both natural and agricultural environments.